Vidova gora i sveti VidDie Vidova gora auf Brač und Sankt-Veit - Katičić, Radoslav (Studia mythologica Slavica, 2010)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A widespread and often repeated notion that Vidova gora on the island of Brač is named after the pagan Slavic god Vid is here subjected to a thorough critical review. Numerous churches of St. Vitus in the Western South Slavic area, especially in the Adriatic, including the Rijeka Cathedral, are continuing the cult of the Slavic god Sventovit, well known from the Early Middle Ages on the Baltic Sea island of Rügen, in a specific Christian form. As a result, it follows that St. Vitus among the Adriatic Slavs actually occurs as interpretatio christiana, but of the thunder-god Perun. The god Sventovit was confirmed only among the Baltic and Polap Slavs. On the other hand, the name of Vid instead of Vit for Latin Vitus derived from paretymology encouraged by South Slavic, not pre-Slavic, folk beliefs. As for Vid as the name of the Slavic pagan god, there are no confirmations. Despite the etymological uncertainties, the name Sventovit for its meaning could be understood as a ritual invocation or nickname of Perun, and so could be the case in Rügen. Due to the great similarity of the names, the name Sventovit could have had the effect that the Christian veneration of St. Vitus replaced the pagan worship of the pagan thunder-god.